(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
Gaulish is a language in the Celtic language family, documented in Gaul (France and surrounding territories) from around the 2nd century BC and through the Roman period. This idiom is presented primarily in Greek (Gallo-Greek) and Latin (Gallo-Latin) script, with a small number of Gaulish texts also attested in Etruscan alphabet in Italy (Gallo-Etruscan) and Gaulish names in Iberian script. In this article we detail our knowledge of the linguistic content, context and classification of Gaulish, and consider the epigraphic corpus, naming practices, writing systems and the cultural interactions that shape this material. Finally, we discuss the future challenges for the study of Gaulish and some of the work that is underway which will drive our research in the 21st century.